Предмет: Алгебра,
автор: nelka199924
упростите выражение:
(3+2√2)(1-√2)^2=
(√3-1)^2(4+2√3)=
(7+4√3)(2-√3)^2=
(√2-3)^2(11+6√2)=
Ответы
Автор ответа:
0
(3+2√2)(1-√2)^2=(3+2√2)(1-2√2+2)=3-6√2+6+2√2-8+4√2=1
(√3-1)^2(4+2√3)=(3-2√3+1)(4+2√3)=12+6√3-8√3-12+4+2√3=4
(7+4√3)(2-√3)^2=(7+4√3)(4-4√3+3)=28-28√3+21+16√3-48+12√3=1
(√2-3)^2(11+6√2)=(2-6√2+9)(11+6√2)=22+12√2-66√2-72+99+54√2=49
(√3-1)^2(4+2√3)=(3-2√3+1)(4+2√3)=12+6√3-8√3-12+4+2√3=4
(7+4√3)(2-√3)^2=(7+4√3)(4-4√3+3)=28-28√3+21+16√3-48+12√3=1
(√2-3)^2(11+6√2)=(2-6√2+9)(11+6√2)=22+12√2-66√2-72+99+54√2=49
Похожие вопросы
Предмет: Геометрия,
автор: Аноним
Предмет: Русский язык,
автор: Аноним
Предмет: Математика,
автор: Dariya373
Предмет: Информатика,
автор: DashaSwag
Предмет: Алгебра,
автор: kotika1975